Modelling the carbonated concrete realkalization - Jaśniok, Mariusz; Zybura, Adam (Journal of Civil Engineering and Management, 2009)
The presented model of carbonated concrete realkalization is compiled on the basis of the multi‐component medium theory equations. The process equations have been obtained from an analysis of the partial equations of mass, electric charge, momentum, energy, and entropy inequality. The experimental testing reported is related to a theoretical model which determines changes of ion concentrations in the pore solution of the cover, as a result of the realkalization. On the basis of the test results, the process equations have been simplified and formally transformed into the form of an equation for the OH– ions flow, coupled with the Na+ions transport. By solving the converse problem of this equation, the determinant OH– ions electro‐diffusion coefficient is calculated and then, after taking the experimental test results into account, its numerical values, the range of stable solutions and the influence of the process non‐stationariness are determined.SantraukaKarbonatizavusio betono šarminės terpės atkūrimo modelis sudarytas remiantis daugiakomponentės aplinkos teorijos lygtimis. Procesą aprašančios lygtys sudarytos atlikus masės balanso, elektros krūvio, judesio kiekio, energijos, taip pat entropijos nevienodumo parcialinių lygčių analizę. Eksperimentiniai tyrimai susieti su teoriniu modeliu apibrėžiant jonų koncentracijos pokytį tirpale apsauginio sluoksnio porose atkuriant šarminę terpę. Remiantis bandymų rezultatų analize, procesą aprašančios lygtys supaprastintos ir formaliai pertvarkytos į lygtis, aprašančias OH¯ jonų, susietų su Na+ jonais, pernešimu. Išsprendus šį uždavinį atvirkštiniu keliu, išreikštas OH¯ jonų elektrodifuzijos koeficientas ir, remiantis eksperimentinių tyrimų rezultatais, nustatyta jo skaitinė reikšmė, sunkiai skaidomų tirpalų sritis, taip pat proceso nepastovumo įtaka.First Published Online: 14 Oct 2010Reikšminiai žodžiai: betonas, armatūros korozija, elektrocheminis šarminės terpės atkūrimas, eksperimentiniai tyrimai, proceso modeliavimas.